2007
DOI: 10.1111/j.1542-474x.2007.00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable Interatrial Conduction Illustrated in a Hypertrophic Cardiomyopathy Population

Abstract: The present study suggests that the longer P-wave duration observed in HCM patients may be explained by a higher prevalence of block in one or more of the interatrial conduction routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
51
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 32 publications
6
51
2
Order By: Relevance
“…The P wave morphology was subsequently automatically classified into one of three predefined classes described earlier 13,16,17 …”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…The P wave morphology was subsequently automatically classified into one of three predefined classes described earlier 13,16,17 …”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…25,26 Unfiltered, signal-averaged P waves were analyzed to determine P wave morphology. 19,20,24,25 Following high-pass (0.5 Hz) and bandstop (50 Hz) filtering the QRS complexes were 4 automatically identified and grouped according to similarity (a cross-correlation coefficient, ρ > 0.9). P waves were extracted using 250 ms wide signal windows preceding each QRS complex.…”
Section: Data Acquisition and Analysismentioning
confidence: 99%
“…[19][20][21] It was recently suggested that the three different P wave morphology classes that have been identified (Figure 1), [19][20][21] arise from differences in interatrial conduction. 20 If confirmed, this 2 may vastly improve clinical diagnostic abilities in the case of atrial arrhythmia. The differences between the observed P wave morphology classes are primarily seen in the terminal portion of the P wave, and are therefore likely to reflect foremost differences in left atrial activation.…”
Section: Introductionmentioning
confidence: 99%
“…24 All control subjects, including the athletes, were asymptomatic volunteers with no evidence of cardiac disease based on a negative history and physical examination. The athletes comprised Swedish triathletes as well as semi-professional soccer and handball players of both genders who had cardiac magnetic resonance imaging scans demonstrating no evidence of HCM or any other clinical pathology.…”
Section: Methodsmentioning
confidence: 99%
“…High-fidelity (1000 samples/sec/channel) ECG systems from Siemens-Elema AB (Solna, Sweden), 24 or Cardiax/CardioSoft (Budapest, Hungary/Houston, TX) 21,25 were utilized to acquire a minimum of 256 waveforms acceptable for both signal averaging and variability analyses (see below). Imaging was performed using standard clinical techniques as previously described, 24,26 with the clinicians who produced the clinical imaging reports being blind to the A-ECG results, which were in turn produced in the automated fashion described below.…”
Section: Methodsmentioning
confidence: 99%